2021
DOI: 10.7554/elife.69160
|View full text |Cite
|
Sign up to set email alerts
|

GIV/Girdin, a non-receptor modulator for Gαi/s, regulates spatiotemporal signaling during sperm capacitation and is required for male fertility

Abstract: For a sperm to successfully fertilize an egg, it must first undergo capacitation in the female reproductive tract and later undergo acrosomal reaction (AR) upon encountering an egg surrounded by its vestment. How premature AR is avoided despite rapid surges in signaling cascades during capacitation remains unknown. Using a combination of conditional knockout (cKO) mice and cell-penetrating peptides, we show that GIV (CCDC88A), a guanine nucleotide-exchange modulator (GEM) for trimeric GTPases, is highly expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…PPARγ can control this process via glucose metabolic activity and other pathways, enhancing capacitated sperm motility and thus serving as an important intermediary between metabolic activity and male fertility. Chen et al observed PPARγ and cAMP to synergistically regulate gene expression, and others have found the activation of PPARγ to influence the cAMP-mediated signaling pathway through mechanisms linked to the regulation of PKA. , The activation of PPARγ can also reportedly regulate components of the PI3K signaling cascade in several cell types, fully activating the major downstream gene AKT in the PI3K signal transducer . GSEA data from this study revealed that CAP sperm exhibited the significant downregulation of the PI3K-Akt signaling pathway gene set, in line with prior studies demonstrating that PI3K-Akt-dependent actin polymerization in the sperm tail necessitates both PKA and protein Tyr-P modification in the context of sperm capacitation. , Sperm tail PI3K-Akt signaling enhancement has also been linked to enhanced motility and survival in the context of capacitation, while in the sperm head such signaling can suppress cAMP surges and premature AR induction. ,, …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…PPARγ can control this process via glucose metabolic activity and other pathways, enhancing capacitated sperm motility and thus serving as an important intermediary between metabolic activity and male fertility. Chen et al observed PPARγ and cAMP to synergistically regulate gene expression, and others have found the activation of PPARγ to influence the cAMP-mediated signaling pathway through mechanisms linked to the regulation of PKA. , The activation of PPARγ can also reportedly regulate components of the PI3K signaling cascade in several cell types, fully activating the major downstream gene AKT in the PI3K signal transducer . GSEA data from this study revealed that CAP sperm exhibited the significant downregulation of the PI3K-Akt signaling pathway gene set, in line with prior studies demonstrating that PI3K-Akt-dependent actin polymerization in the sperm tail necessitates both PKA and protein Tyr-P modification in the context of sperm capacitation. , Sperm tail PI3K-Akt signaling enhancement has also been linked to enhanced motility and survival in the context of capacitation, while in the sperm head such signaling can suppress cAMP surges and premature AR induction. ,, …”
Section: Discussionsupporting
confidence: 86%
“…75,76 Sperm tail PI3K-Akt signaling enhancement has also been linked to enhanced motility and survival in the context of capacitation, while in the sperm head such signaling can suppress cAMP surges and premature AR induction. 75,77,78 Fatty acid-binding protein 3 (FABP3) functions to promote fatty acid uptake and intracellular transport such that these macromolecules can undergo appropriate metabolic processing, thereby regulating gene expression and associated cell growth activity. 79 Dynamic shifts in sperm fatty acid composition are linked to fertilizing ability, and FABPs may play a role in regulating this process.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we identify and characterize a chemical probe of broad utility for dissecting atypical mechanisms of cellular communication mediated by G-proteins with important biomedical implications not only for cancer, but also for fibrosis, and male fertility, among other maladies (8, 9, 17, 18, 20, 40, 41). Because its chemical scaffold is synthetically tractable, IGGi-11 may further serve as a lead compound to develop analogs with improved potency and pharmacokinetic properties that could have therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we identify and characterize a chemical probe of broad utility for dissecting atypical mechanisms of cellular communication mediated by G-proteins with important biomedical implications not only for cancer, but also for fibrosis, and male fertility, among other maladies (8,9,17,18,20,40,41).…”
Section: Discussionmentioning
confidence: 99%